1999
DOI: 10.3109/03005369909090112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics Applied to Clinical Practice: The Cx26 Hearing Impairment

Abstract: Mutations in the Cx26/GJB2 gene account for a large proportion of pre-lingual hearing impairment with a prevalence up to 50% in autosomal recessive cases and a still undefined prevalence in sporadic cases. Ninety-four subjects affected by non-syndromal sensorineural hearing impairment (NSHI) were enrolled in the study. The patients had either a family history of childhood hearing deficit or represented sporadic cases. The risk of an acquired cause of the deficit has been carefully excluded. Audiological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 7 publications
3
27
2
Order By: Relevance
“…There is, however, some controversy regarding genotype/phenotype correlation (Cohn et al 1999;Cryns et al 2004;Denoyelle et al 1999;Estivill et al 1998;Murgia et al 1999;Orzan et al 1999). For example, prediction of the degree of hearing loss was difficult, and environmental factors as well as modifier genes may have been involved (Cohn et al 1999;Murgia et al 1999;Orzan et al 1999). On the other hand, a series of reports have indicated that certain phenotypes are dependent on certain genotypes (Denoyelle et al 1999;Estivill et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, some controversy regarding genotype/phenotype correlation (Cohn et al 1999;Cryns et al 2004;Denoyelle et al 1999;Estivill et al 1998;Murgia et al 1999;Orzan et al 1999). For example, prediction of the degree of hearing loss was difficult, and environmental factors as well as modifier genes may have been involved (Cohn et al 1999;Murgia et al 1999;Orzan et al 1999). On the other hand, a series of reports have indicated that certain phenotypes are dependent on certain genotypes (Denoyelle et al 1999;Estivill et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that genetic testing to determine the cause of deafness facilitates prediction of the course of hearing loss and prognostication of language development. There is, however, some controversy regarding genotype/phenotype correlation (Cohn et al 1999;Cryns et al 2004;Denoyelle et al 1999;Estivill et al 1998;Murgia et al 1999;Orzan et al 1999). For example, prediction of the degree of hearing loss was difficult, and environmental factors as well as modifier genes may have been involved (Cohn et al 1999;Murgia et al 1999;Orzan et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As in the French study discussed above, the 35⌬G homozygotes fell into the moderate or profound range, whereas the compound heterozygotes were dispersed among the three categories (moderate, severe, and profound), suggesting allelic difference in expressivity. 23 Seven additional studies presented data regarding the severity of hearing loss among individuals with GJB2 variants. Because the number of alleles and, therefore, the number of possible genotypes was large, the absolute numbers of cases for each genotype in the studies combined were small.…”
Section: Severity Of Hearing Lossmentioning
confidence: 99%
“…Likewise, Orzan et al reported three Italian children with biallelic GJB2 genotypes who had a sudden onset of hearing loss between 18 and 24 months of age, although it is not clear whether prior hearing status was formally documented or based on parental report. 23 Recent research has not focused on rigorous analysis of the possible contribution of GJB2 to postlingual hearing loss. Four published studies have included individuals with postlingual hearing loss.…”
Section: Type Of Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation